A new species and a new record of the subgenus Dilatognathus Kluge 2012 (Ephemeroptera: Leptophlebiidae: genus Choroterpes Eaton, 1881) from India - Selvakumar, C.; Subramanian, K. A.; Chandra, Kailash; Sivaramakrishnan, K. G.; Jehamalar, E. Eyarin; Sinha, Bikramjit (Zootaxa, 2017)
A new species belonging to the subgenus Dilatognathus of the genus Choroterpes is described based on larvae collected from Andaman and Nicobar Islands. Choroterpes (Dilatognathus) nicobarensis n. sp. can be distinguished from all other species of Dilatognathus by the absence of a tusk on the maxillary apex, has ventro-apical flange and dentiseta directed distally, as in Choroterpes other than Dilatognathus. Choroterpes (Dilatognathus) nigella (Kang & Yang 1994) is newly recorded based on larvae collected in Arunachal Pradesh, Meghalaya and West Bengal. Remarks on the evolution of the mouth apparatus of the subgenus Dilatognathus are given.